Análise da viabilidade de carteiras compostas por índices das bolsas de valores dos países que integram o BRIC - Coelho, Paula Augusta Rodrigues (2010)
Investors try to capture the opportunities for capital gains offered by emerging countries by increasing the total return or reduce the risk of the portfolio. Solnik (1991, 2004) found evidence of reduced risk and increased return through international diversification. In addition, to benefits such as the development of local capital markets, the greater liquidity of shares traded and financial market development. This study aims to determine whether markets are more globalized and investigate whether there are still benefits of risk-return in the international diversification of portfolios for an investor from United States. The countries of the sample will be the three largest stock markets (U.S., Japan and England) and the BRICs (Brazil, China, Russia and India). The study refers to two periods: from January 1996 to December 2000 and from January 2003 to December 2007. In the second period (2003-2007) the market indexes are more correlated and has a higher level of NGR, ie, the markets of the sample are more global. Using the Model Portfolio Selection, met the efficient portfolio for the investor of the United States. The results show that the portfolio composed with developed countries indexes (United Kingdom, United States of America and Japan) and indexes of the countries that make up the BRIC (Brazil, Russia, India and China) has a better risk-return than the portfolio formed only by developed countries index, indicating that despite of the increased globalization, there is still diversification benefits in the developing countries